THE MEANINGS OF CARE DURING CHILDBIRTH: AN INTERGENERATIONAL STUDY - Natália Rejane Salim; Glauce Cristine Ferreira Soares; Jacqueline Isaac Machado Brigagão; Dulce Maria Rosa Gualda (Universidade Federal do Paraná, 2012)
This research, with a qualitative approach, aimed to study the meanings attributed to care in childbirth and analyze how the different care practices in Obstetrics are present in the discourse of the women from different generations of the same family. Open interviews were undertaken which developed as conversations, making it possible to share histories and meanings. The analysis prioritized dialog maps, making it possible to visualize the meanings which the women attribute to the different care practices which they received, and the effect of these practices on each one's experience. The interviews' analysis made it possible to identify two categories: The meanings of the care during childbirth and The meanings attributed to the experience of the pain of childbirth. The results show the sharing of repertoires and different types of care during childbirth and of context of the experiences, and their effects on the meanings attributed.